AKTIVITAS DAN ISOLASI SENYAWA BIOAKTIF DARI EKSTRAK ETIL ASETAT DAUN TEH (Camellia sinensis (L.) Kuntze) SEBAGAI PENGHAMBATAN ENZIM α-GLUKOSIDASE - Nuraini Saadah; Lilik Sulastri; Syamsoedin Abdilah; Partomuan Simanjuntak (PROSIDING SEMINAR KIMIA, 2023)
Tea (Camellia sinensis (L.) Kuntze) is one of the plants that has compounds that have the potential as inhibitors of the α-glucosidase enzyme. The purpose of this study was to know the activity of chemical compounds in the ethyl acetate extract of tea leaves as an inhibitor of the α-glucosidase enzyme. Extraction tea leaf was carried out by maceration tea leaf powder in ethanol 96% 3 times, then partitioned with ethyl acetate and water. The ethyl acetate extract obtained was determined by the inhibitory activity of the -glucosidase enzyme, then fractionated by column chromatography (SiO2; n-hexane: ethyl acetate 10:1 ~ 1:1) yielding 10 fractions (CSEA-1 ~ CSEA-10). The CSEA-2 fraction was further fractionated by column chromatography (SiO2; n-hexane: ethyl acetate 20:1 ~ 1:1) yielding 9 fractions (CSEA-2.1~ CSEA-2.9). The results showed that the ethyl acetate extract had activity with an IC50 value of 45.04 ppm, the fractionated CSEA-2.1 subfraction had an IC50 value of 41.51 ppm with acarbose as a comparison of 19.24 ppm. The conclusion is that the CSEA-2.1 subfraction has better activity than the extract in inhibiting the α-glucosidase enzyme and can be used as an alternative candidate for diabetes drugs. Keywords: Camellia sinensis (L.) Kuntze, tea, α-glucosidase enzyme inhibitor, Indonesian medicinal plant, IC50